A SEMANTIC ANALYSIS ON THE ENGLISH TRANSLATION OF SURAH LUQMAN - Munawwir Hadiwijaya (UIBU, 2019)
Quran in Islam has role as the highest source which is used in formulating laws, and other regulations concerning the relation between the creature and his creator and creature with other creature. One of surah in Quran is surah Luqman, which consists of many advices of a man whose name is Luqman. It is so special because there are educational aspects which can be learned from this surah. Luqman in delivering his advices is not by the way of saying in a harsh manner, but by the way of full of affection, which is shown in his hearty calling to his son by the word bunayya (my son). In educating be desirable that must be based on or surrounded by the affection feeling to the students. This research tends to be descriptive qualitative research since it does not deal with number at all, which describes about semantics aspects and the message involvement used in the English translation of surah Luqman done by Taqqi-ud-Din and Muhsin Khan. The result shows that there are three categories of meaning can be found in this discussion, they are lexical meaning, sentential meaning, and discourse meaning, they almost can be found in every part of surah Luqman. Moreover, there are several messages involved in surah Luqman such as, they are Quran guarantee the success of people who believe in God, the advisees of Luqman to his son, and the authority of God upon this universe is absolute and the impact of denial of it.